2022
DOI: 10.1021/acssuschemeng.2c01632
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting an Efficient and Stable Catalyst for the Selective Oxidation of 5-Hydroxymethylfurfural to 2,5-Diformylfuran by Incorporating Vanadium in the Framework of Hydroxyapatite

Abstract: Hydroxyapatite displays immense potential in catalysis because of its properties to form doped single and multiphasic systems. In the present study, vanadium-incorporated hydroxyapatite was investigated for aerobic oxidation of 5-hydroxymethylfurfural to 2,5-diformylfuran. The amount of vanadium precursor and the pH in catalyst synthesis were significant factors in defining the catalytic properties of V-HAP. The morphologies and structures of the catalysts were well studied. Field emission scanning electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…Except the above‐mentioned noble metals, V has also been widely utilized in this transformation. In general, various V species with chemical valences of V 5+ or V 4+ have been loaded to different carriers, such as H‐Beta, [39] metal oxides, [40] activated carbon, [41] carbon nanotubes, [42] carbon spheres, [43] ceramic powders, [44] hydroxyapatite (HAP) [45] and zeolites, [46] etc (as listed in Table 2).…”
Section: Hmf‐dff‐ffca‐fdca Reaction Pathmentioning
confidence: 99%
“…Except the above‐mentioned noble metals, V has also been widely utilized in this transformation. In general, various V species with chemical valences of V 5+ or V 4+ have been loaded to different carriers, such as H‐Beta, [39] metal oxides, [40] activated carbon, [41] carbon nanotubes, [42] carbon spheres, [43] ceramic powders, [44] hydroxyapatite (HAP) [45] and zeolites, [46] etc (as listed in Table 2).…”
Section: Hmf‐dff‐ffca‐fdca Reaction Pathmentioning
confidence: 99%
“…Our research group has effectively combined earth-abundant transition metals with natural clay and a SiO 2 –Al 2 O 3 support system for excellent selectivity of biodiesel and bio jet fuel. ,, Researchers have investigated the catalytic role of HAP, a biomineral that is a major component of bones and teeth (50% by volume and 70% by weight) . The hydroxyapatite (HAP) support catalyst also exhibits several outstanding qualities, including higher surface area, superior thermal stability, and acid–base properties . The naturally abundant, minerals-loaded HAP catalyst was explored in catalytic reactions .…”
Section: Introductionmentioning
confidence: 99%
“…[40] In a similar direction, Zhao et al reported selective oxidation of 5hydroxymethylfurfural to 2,5-diformylfuran using vanadium incorporated HAP at 150 °C in DMSO and 15 mL/min O 2 with 78 % conversion and 63 % yield. [41] Very recently, Hau et al used Pd/HAP catalyst for oxidation of glycerol to glyceric acid under aqueous basic conditions and 10 bar O 2 at 80 °C and achieved 59 % conversion with 90 % selectivity for glyceric acid. [42] Though the catalytic activities of hydroxyapatite-supported catalysts have been explored for various oxidation reactions, additive-free aerial oxidation of HDO and related diols is rarely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar direction, Zhao et al . reported selective oxidation of 5‐hydroxymethylfurfural to 2,5‐diformylfuran using vanadium incorporated HAP at 150 °C in DMSO and 15 mL/min O 2 with 78 % conversion and 63 % yield [41] . Very recently, Hau et al .…”
Section: Introductionmentioning
confidence: 99%